2023
DOI: 10.3390/vaccines11030625
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of the Acceptance of Anti COVID-19 Vaccine in Urban and Rural Settings in Cameroon

Abstract: The COVID-19 pandemic rapidly evolved in December 2019 and to prevent its spread, effective vaccines were produced and made available to the population. Despite their availability so far in Cameroon, the vaccination coverage remains low. This study aimed at describing the epidemiology of the acceptance of vaccines against COVID-19 in some urban and rural areas of Cameroon. A cross-sectional, descriptive and analytical survey was conducted from March 2021 to August 2021 targeting unvaccinated individuals from u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Kamga et al in 2018 in the same study site reported a similar female predominance of 68.63% (105/153) and their mean age was 30.4 years ±5.63 years [ 25 ]. While several studies in community settings in Cameroon have also found similar women predominance trend [ 26 29 ], contrary results were more or less reported in rural area of foreign countries including Congo [ 30 ], Egypt [ 31 ], China [ 32 ], in the USA [ 33 ]. In fact, the Cameroonian demographics reflects in general more women than men and also a relative young population.…”
Section: Discussionmentioning
confidence: 95%
“…Kamga et al in 2018 in the same study site reported a similar female predominance of 68.63% (105/153) and their mean age was 30.4 years ±5.63 years [ 25 ]. While several studies in community settings in Cameroon have also found similar women predominance trend [ 26 29 ], contrary results were more or less reported in rural area of foreign countries including Congo [ 30 ], Egypt [ 31 ], China [ 32 ], in the USA [ 33 ]. In fact, the Cameroonian demographics reflects in general more women than men and also a relative young population.…”
Section: Discussionmentioning
confidence: 95%
“…This table presents liver impairment according to hepatitis C antibodies carriage (HCVAb) [26]. While several studies in community settings in Cameroon have also found similar women predominance trend [27,28,29,30], contrary results were more or less reported in rural area of foreign countries including Congo [31], Egypt [32],…”
Section: Liver Impairment According To Hepatitis C Antibodies Carriag...mentioning
confidence: 96%